High-performance self-textured high-temperature piezoelectric ceramic, preparation method and application
Patent Information
- Application Number
- CN202611218469.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-30
AI Technical Summary
现有技术通过添加氧化物助烧结剂(如氧化铜、氧化硼或BaO-2B2O3共晶体等)来诱导陶瓷的织构化,但由于氧化物助烧结剂在陶瓷晶格中的离子位置及分布状态无法精确确定,其诱导晶粒定向生长的微观机制缺乏深入揭示,导致性能优化缺乏明确的理论指导
Smart Images

Figure CN123003286A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of new materials technology, and in particular to a high-performance self-textured high-temperature piezoelectric ceramic, its preparation method, and its application. Background Technology
[0002] Piezoelectric materials, as functional materials for converting mechanical energy into electrical energy, have wide applications in aerospace, biology, information technology, nuclear energy, and artificial intelligence. Especially with the rapid development of modern industry, the demand for piezoelectric conversion materials in harsh environments such as high temperatures is becoming increasingly urgent. Currently, the piezoelectric products on the market are mainly based on lead zirconate titanate (Pb(Zr,Ti)O3) ceramics. Although they have excellent overall electrical properties, their Curie temperature Ti is relatively low. C With a operating temperature range of only 250-380 °C, PZT ceramics undergo severe aging when the operating temperature exceeds 150 °C, making them unsuitable for manufacturing high-temperature piezoelectric devices. Furthermore, PZT ceramics contain high levels of lead, posing serious health risks to humans and the environment. In contrast, bismuth layered piezoelectric materials, due to their superior mechanical properties, low dielectric loss, and high Curie temperature, possess significant application potential in high-temperature applications exceeding 650 °C, making them a preferred material for the core sensing element of high-temperature piezoelectric vibration sensors and thus attracting considerable attention. Among these, calcium bismuth niobate (CaBi₂Nb₂O₉) boasts the highest Curie temperature among bismuth layered compounds (T0). C With a temperature range of ~940 ℃, these materials hold promise for applications in ultra-high temperature environments. However, their layered structure restricts spontaneous polarization to a two-dimensional level, resulting in a low piezoelectric coefficient and poor temperature stability and high-temperature insulation properties, limiting their further application in high-temperature piezoelectric devices. Studies show that piezoelectric performance parallel to the ab plane is superior to that perpendicular to it. By applying external forces, such as magnetic, mechanical, or electric fields, grains can be oriented to form a texture, resulting in a large piezoelectric coefficient in textured ceramics parallel to the ab plane. However, these special processes are costly, complex, and unsuitable for large-scale manufacturing.
[0003] There is an existing method that uses oxides as sintering aids to achieve texture (Chinese Patent Publication CN114560698A, A method for inducing texture enhancement of calcium bismuth niobate high-temperature piezoelectric ceramics by oxide sintering aids). This invention uses the method of adding oxide sintering aids to prepare textured bismuth layered high-temperature piezoelectric ceramic materials by solid-state reaction.
[0004] The disadvantages are as follows: 1. The performance control mechanism is unclear and lacks designability. Existing technologies induce ceramic texturing by adding oxide sintering aids (such as copper oxide, boron oxide, or BaO-2B2O3 eutectic). However, because the ionic positions and distribution of these oxide sintering aids in the ceramic lattice cannot be precisely determined, the microscopic mechanisms by which they induce directional grain growth lack in-depth understanding, resulting in a lack of clear theoretical guidance for performance optimization. This "black box" approach makes it difficult to establish a clear correlation between "composition-structure-performance," hindering precise formulation design and performance optimization for different application requirements.
[0005] 2. There is an upper limit to the improvement of texture, making it difficult to break through performance bottlenecks. Existing technologies typically achieve ceramic texture levels of only about 40% to 70%, making it difficult to achieve higher degrees of preferred grain orientation. This lower texture limits the potential for further optimization of piezoelectric properties.
[0006] 3. The introduction of additional components brings potential uncontrollable factors. Existing technologies introduce oxide sintering aid components into the calcium bismuth niobate matrix, which is equivalent to introducing one or more second-phase substances (or solute components) into the original ceramic system. These additional components may lead to the following problems: Increased complexity of ingredients: Higher requirements for the types and metering accuracy of raw materials, strict control over the uniform dispersion of each additive during the preparation process, and more stringent requirements for production operation conditions.
[0007] Compatibility issues: The chemical compatibility between oxide sintering aids and matrix materials needs to be strictly matched; otherwise, an unfavorable second phase may be formed, affecting the densification degree and final properties of the ceramic.
[0008] Reduced performance stability: Uneven distribution of trace amounts of sintering aids may lead to performance fluctuations between batches, making it difficult to guarantee the stability and repeatability of product quality.
[0009] By comparison, this invention differs fundamentally from the aforementioned prior art. Addressing the problems of the prior art, this invention provides a method for achieving high-performance self-textured high-temperature piezoelectric ceramics. This invention employs a method of doping one or more metal ions at Ca, Bi, or Nb sites, utilizing a simple solid-state reaction method to prepare high-texturation self-textured high-temperature piezoelectric ceramics with a bismuth layered structure possessing excellent ferroelectric and piezoelectric properties under conditions without electric fields, magnetic fields, or mechanical stress. Summary of the Invention
[0010] The purpose of this invention is to overcome the shortcomings of the prior art and provide a high-performance self-textured high-temperature piezoelectric ceramic, its preparation method, and its application.
[0011] The technical solution adopted by this invention to solve its technical problem is: A high-performance self-textured high-temperature piezoelectric ceramic, wherein the chemical formula of the piezoelectric ceramic is: Ca 1-x A x Bi 2-y B y Nb 2- z C z O9; where x, y, and z all take values greater than or equal to 0 and less than or equal to 1, and x, y, and z cannot all take the value 0 at the same time; A represents one or more metal ions that substitute for the Ca site; B represents one or more metal ions that substitute for the Bi site; C represents one or more metal ions that substitute for the Nb site; Furthermore, the piezoelectric ceramic is sintered using a conventional solid-state reaction method without adding any oxide sintering aids or applying electric, magnetic, or mechanical stresses, and its texture is ≥90%.
[0012] Furthermore, A is selected from: Li + Na + 、Sr 2+ Ba 2+ Mg 2+ La 3+ 、Nd 3+ 、Sm 3+ One or more of the following; The B is selected from: La 3+ 、Nd 3+ 、Sm 3+ Gd 3+ Y 3+ Ce 3+ Cu 2+ One or more of the following; The C is selected from: Ta 5+ W 6+ V 5+ Ti 4+ Co 6+ Mn 4+ Cu 2+ One or more of them.
[0013] Furthermore, the residual polarization intensity of the piezoelectric ceramic reaches 15 μC / cm. 2 The above represents the remanent magnetization of the high-temperature piezoelectric ceramic CaBi₂Nb₂O₉, which is 4.7 μC / cm. 2 More than 3 times that of the CaBi2Nb2O9 high-temperature piezoelectric ceramic; the piezoelectric coefficient reaches 10 pC / N, which is more than 2 times the piezoelectric coefficient of 5 pC / N of the CaBi2Nb2O9 high-temperature piezoelectric ceramic.
[0014] The piezoelectric ceramics described above are used as piezoelectric devices.
[0015] A method for preparing piezoelectric ceramics as described above includes the following steps: Step 1: Weigh calcium carbonate, bismuth trioxide, niobium pentoxide and dopant, and add them to a mortar or ball mill in sequence, and grind for 1-2 hours. Step 2: The ground powder is loaded into an 8-30 mm tableting mold and pressed into tablets on a tableting machine at a pressure of 8-25 tons. Then, it is pre-sintered in a high-temperature furnace and cooled with the furnace after sintering to obtain a sheet sample. Step 3: Grind the sintered sheet sample from Step 2 again in a mortar or ball mill for 1-2 hours. Then, put the ground powder into an 8-30 mm tableting mold and press it into a tablet press at a pressure of 8-25 tons. Then, heat it to 950-1200 ℃ in a high-temperature furnace at a heating rate of 3℃ / min, hold it at that temperature for 3-5 hours, and then cool it in the furnace to obtain piezoelectric ceramics. The resulting sheet sample is the piezoelectric ceramic.
[0016] Furthermore, in step 1, the molar ratio of calcium, bismuth, niobium, and dopant elements is determined based on the doping location and the type of dopant element.
[0017] Furthermore, in step 2, the pre-sintering can be a one-step sintering, a two-step sintering, or a three-step sintering. The sintering temperature is 800-950 ℃, the sintering time is 2-5 h, and the heating rate is controlled at 3-5 ℃ / min, which can be flexibly adjusted according to performance requirements.
[0018] In step 3, the final sintering temperature and sintering time are flexibly adjusted according to performance requirements.
[0019] Furthermore, the method also includes step 4: depending on the requirements, the sheet sample sintered in step 3 is ground again in a mortar or ball mill for 1-2 hours, and then the ground powder is loaded into a tableting mold of 8-30 mm and pressed into tablets on a tableting machine at a pressure of 8-25 tons; then the temperature is raised to 1000-1200 ℃ in a high-temperature furnace at a heating rate of 3 ℃ / min, held for 3-5 hours, and then cooled in the furnace to obtain piezoelectric ceramics.
[0020] The advantages and positive effects of this invention are as follows: 1. Achieve ultra-high texture and break through performance bottlenecks This invention can achieve an ultra-high lotgering factor of over 90%, which is significantly superior to existing technologies (such as the oxide sintering aid method, which achieves a maximum of only about 70%) (see...). Figure 7 This significantly enhances the preferred orientation of the grains, thus increasing the piezoelectric constant d. 33 Ferroelectric properties (see) Figure 8 Both high-temperature stability and high-temperature stability are synergistically improved.
[0021] 2. Pure ingredients and clear performance regulation mechanism. This invention does not add any oxide sintering aids, thus avoiding problems such as uncertain occupancy of foreign components in the crystal lattice, second phase formation, and performance fluctuations. Dopant ions precisely enter the Ca, Bi, or Nb lattice positions, establishing a clear "doping-texture-structure-performance" correlation, exhibiting excellent designability and repeatability.
[0022] 3. The preparation process is extremely simple, resulting in significant cost advantages. This invention uses only the traditional solid-state reaction method, without the need for any external field (electric field, magnetic field, mechanical stress) or special inducer (template, sintering aid), with a short process flow, wide operating window, significantly reduced manufacturing costs, and easy industrial scale-up production.
[0023] 4. Excellent overall ferroelectric and electrostatic performance This invention achieves high texture while maintaining a high Curie temperature (≥900 ℃) (see...). Figure 9 This method simultaneously enhances piezoelectric activity, solving the problem of performance trade-offs in traditional methods. It is particularly suitable for sensor and transducer applications in harsh environments such as high temperatures.
[0024] 5. Uniform microstructure and good batch stability This invention induces texture through intrinsic ion substitution rather than added phases, resulting in more uniform ceramic grain size distribution, higher density, and smaller batch-to-batch performance differences, providing a material basis for the reliability of high-end piezoelectric devices.
[0025] 6. Precise doping design of lattice sites This invention relates to calcium bismuth niobate (CaBi₂Nb₂O₉, CBNO)-based ceramics, which selectively incorporate metal ion doping at one or more sites among Ca, Bi, or Nb sites, rather than through the addition of external sintering aids or templates. The type, combination, and proportion of dopant ions are the core determinants of self-texturing behavior and properties.
[0026] 7. A pure system without any added additives The material composition of this invention is limited to the CBN matrix and doped ions, without the addition of any oxide sintering aids or other texture inducers. This not only simplifies the composition but also avoids the uncontrollable performance problems caused by the uncertainty of foreign ion occupancy.
[0027] 8. Conventional solid-state reaction method and conventional sintering This invention uses the most common solid-state reaction method in industry (ball milling, drying, pressing, sintering), without the need for special equipment (such as hot pressing, spark plasma sintering (SPS), tape casting, etc.), and without the need to apply electric field, magnetic field or mechanical stress during the sintering process.
[0028] 9. Conditions for achieving ultra-high texture This invention achieves a ceramic lotgering factor of ≥90% by matching the doping components with the sintering process (such as sintering temperature, holding time, heating rate, etc.), which is far higher than the existing sintering aid method (≤70%).
[0029] 10. In view of the shortcomings of the prior art, the present invention can precisely control the lattice occupancy and crystal field environment of the doped ions by doping and substituting specific metal ions at Ca sites, Bi sites or Nb sites, thereby achieving predictable and designable control of texture behavior and electrical properties from the structural source.
[0030] To address the second shortcoming of the existing technology, this invention utilizes an ion-doped induced self-texturing method, achieving a significant improvement in texture degree exceeding 90%. This greatly enhances the preferred orientation of the grains, resulting in superior ferroelectric and piezoelectric properties. This effect represents a significant technological advancement that would have been difficult for someone skilled in the art to anticipate using existing technology.
[0031] To address the shortcomings of existing technologies (3), this invention leverages the self-texturing capability of the bismuth calcium niobate matrix, directly regulating the intrinsic crystal properties through ion substitution. This eliminates the need for additional sintering aids, resulting in purer composition, a wider process window, and superior performance consistency.
[0032] 11. The residual polarization of the self-textured high-temperature piezoelectric ceramic prepared by this invention reaches 10 μC / cm. 2 The above represents the remanent magnetization of the high-temperature piezoelectric ceramic CaBi₂Nb₂O₉ (4.7 μC / cm). 2 The piezoelectric coefficient is more than twice that of CaBi2Nb2O9 high-temperature piezoelectric ceramics (5 pC / N); the piezoelectric coefficient reaches 15 pC / N, which is more than three times that of CaBi2Nb2O9 high-temperature piezoelectric ceramics (5 pC / N), which is extremely beneficial to the practical application of the target product. Attached Figure Description
[0033] Figure 1 The image shows the X-ray diffraction (XRD) pattern of the high-performance self-textured high-temperature piezoelectric ceramic prepared in Example 1 of this invention. Figure 2 This is a texture diagram of the high-performance self-textured high-temperature piezoelectric ceramic obtained in Example 1 of this invention; Figure 3 This is a scanning electron microscope (SEM) image of the high-performance self-textured high-temperature piezoelectric ceramic prepared in Example 1 of this invention; Figure 4 The image shows the X-ray diffraction (XRD) pattern of the high-performance self-textured high-temperature piezoelectric ceramic prepared in Example 2 of this invention. Figure 5 This is a texture diagram of the high-performance self-textured high-temperature piezoelectric ceramic obtained in Example 2 of this invention; Figure 6 This is a scanning electron microscope (SEM) image of the high-performance self-textured high-temperature piezoelectric ceramic prepared in Example 2 of this invention. Figure 7 This is a comparison of the texture of bismuth calcium niobate, bismuth calcium niobate with added oxide sintering aid, and bismuth calcium niobate doped with ions in this invention; wherein, from left to right, the samples are bismuth calcium niobate (i.e., pure CBNO), CBNO-oxide sintering aid, and the product obtained in Example 1 of this invention (i.e., doped self-textured CBNO). Figure 8 This is a comparison of the ferroelectric and electroelectric properties of bismuth calcium niobate and bismuth calcium niobate doped with ions in this invention; the samples from left to right are bismuth calcium niobate, i.e., pure CBNO, and the product obtained in Example 1 of this invention (i.e., doped self-textured CBNO). Figure 9 This is a comparison chart of the Curie temperatures of calcium bismuth niobate and doped calcium bismuth niobate in this invention; the samples from left to right are, in order, calcium bismuth niobate (i.e., pure CBNO) and the product obtained in Example 1 of this invention (i.e., doped self-textured CBNO). Detailed Implementation
[0034] The present invention will be further described below with reference to the embodiments. The embodiments described below are descriptive and not limiting, and should not be used to limit the scope of protection of the present invention.
[0035] The various experimental operations involved in the specific embodiments are all conventional techniques in the field. For parts not specifically annotated in this document, those skilled in the art can refer to various commonly used reference books, scientific and technological documents or related instructions and manuals prior to the filing date of this invention to carry out the operations.
[0036] A high-performance self-textured high-temperature piezoelectric ceramic, wherein the chemical formula of the piezoelectric ceramic is: Ca 1-x A x Bi 2-y B y Nb 2- z C z O9; where x, y, and z all take values greater than or equal to 0 and less than or equal to 1, and x, y, and z cannot all take the value 0 at the same time; A represents one or more metal ions that substitute for the Ca site; B represents one or more metal ions that substitute for the Bi site; C represents one or more metal ions that substitute for the Nb site; Furthermore, the piezoelectric ceramic is sintered using a conventional solid-state reaction method without adding any oxide sintering aids or applying electric, magnetic, or mechanical stresses, and its texture degree is ≥90%.
[0037] Furthermore, A is selected from: Li + Na + 、Sr 2+ Ba 2+ Mg 2+ La 3+ 、Nd 3+ 、Sm 3+ One or more of the following; The B is selected from: La 3+ 、Nd 3+ 、Sm 3+ Gd 3+ Y 3+ Ce 3+ Cu 2+ One or more of the following; The C is selected from: Ta 5+ W 6+ V 5+ Ti 4+ Co 6+ Mn 4+ Cu 2+ One or more of them.
[0038] Furthermore, the residual polarization intensity of the piezoelectric ceramic reaches 15 μC / cm. 2 The above represents the remanent magnetization of the high-temperature piezoelectric ceramic CaBi₂Nb₂O₉, which is 4.7 μC / cm. 2 More than 3 times that of the CaBi2Nb2O9 high-temperature piezoelectric ceramic; the piezoelectric coefficient reaches 10 pC / N, which is more than 2 times the piezoelectric coefficient of 5 pC / N of the CaBi2Nb2O9 high-temperature piezoelectric ceramic.
[0039] The piezoelectric ceramics described above are used as piezoelectric devices.
[0040] A method for preparing piezoelectric ceramics as described above includes the following steps: Step 1: Weigh calcium carbonate, bismuth trioxide, niobium pentoxide and dopant, and add them to a mortar or ball mill in sequence, and grind for 1-2 hours. Step 2: The ground powder is loaded into an 8-30 mm tableting mold and pressed into tablets on a tableting machine at a pressure of 8-25 tons. Then, it is pre-sintered in a high-temperature furnace and cooled with the furnace after sintering to obtain a sheet sample. Step 3: Grind the sintered sheet sample from Step 2 again in a mortar or ball mill for 1-2 hours. Then, put the ground powder into an 8-30 mm tableting mold and press it into a tablet press at a pressure of 8-25 tons. Then, heat it to 950-1200 ℃ in a high-temperature furnace at a heating rate of 3℃ / min, hold it at that temperature for 3-5 hours, and then cool it in the furnace to obtain piezoelectric ceramics. The resulting sheet sample is the piezoelectric ceramic.
[0041] Furthermore, in step 1, the molar ratio of calcium, bismuth, niobium, and dopant elements is determined based on the doping location and the type of dopant element.
[0042] Furthermore, in step 2, the pre-sintering can be a one-step sintering, a two-step sintering, or a three-step sintering. The sintering temperature is 800-950 ℃, the sintering time is 2-5 h, and the heating rate is controlled at 3-5 ℃ / min, which can be flexibly adjusted according to performance requirements.
[0043] In step 3, the final sintering temperature and sintering time are flexibly adjusted according to performance requirements.
[0044] Furthermore, the method also includes step 4: depending on the requirements, the sheet sample sintered in step 3 is ground again in a mortar or ball mill for 1-2 hours, and then the ground powder is loaded into a tableting mold of 8-30 mm and pressed into tablets on a tableting machine at a pressure of 8-25 tons; then the temperature is raised to 1000-1200 ℃ in a high-temperature furnace at a heating rate of 3 ℃ / min, held for 3-5 hours, and then cooled in the furnace to obtain piezoelectric ceramics.
[0045] Specifically, the relevant preparation and testing methods are as follows: Example 1: A method for preparing high-performance self-textured high-temperature piezoelectric ceramics, the specific steps of which are as follows: Step 1: Weigh calcium carbonate, bismuth trioxide, niobium pentoxide, vanadium pentoxide, and tantalum pentoxide according to a molar ratio of calcium, bismuth, niobium, vanadium, and tantalum of 1:2:2-2x:x:x (x is greater than 0 and less than or equal to 1). Then, place the calcium carbonate, bismuth trioxide, niobium pentoxide, vanadium pentoxide, and tantalum pentoxide into a mortar in sequence and grind them in a dry environment for 2 hours. Place the ground powder into an alumina crucible and heat it to 800 ℃ in a high-temperature furnace at a heating rate of 3 ℃ / min, hold it at that temperature for 2 hours, and then cool it in the furnace. Step 2: First, put the pre-calcined powder into a mortar and grind it for 2 hours. Then, put the ground powder into a 15 mm tableting mold and press it into tablets on a tablet press with a pressure of 20 tons. Then, heat it to 900℃ in a high-temperature furnace at a heating rate of 3℃ / min, hold it for 2 hours, and then cool it in the furnace to obtain sintered sheet samples. Step 3: The sintered sheet sample from Step 2 is ground again in a mortar for 2 hours. The ground powder is then placed into a 15mm tableting mold and pressed into tablets using a tablet press at a pressure of 8 tons. The temperature is then increased to 1100℃ in a high-temperature furnace at a rate of 3℃ / min, held for 4 hours, and then furnace cooled to obtain a high-performance self-textured high-temperature piezoelectric ceramic with the structural formula CaBi₂Nb. 2- x V x Ta x O9 (x takes values greater than 0 and less than or equal to 1).
[0046] Finally, the target product was characterized using scanning electron microscopy and X-ray diffraction, as shown in the figures below. Figure 1 , Figure 2 and Figure 3 As shown. By Figure 1 As can be seen, the XRD spectrum shows that the relative peak intensity of the target product in the (00l) direction is significantly enhanced, indicating that the target product has a strong (00l) texture parallel to the pressing direction. Figure 2 The texture of the target product is shown to be over 90% for doped calcium bismuth niobate ceramics. Figure 3 The results of scanning electron microscopy (SEM) characterization of the target product show that it consists of densely packed particles. Furthermore, samples with high doping concentrations exhibit distinct grain orientation. Figure 2 and Figure 3 It can be seen that the target product obtained by adding oxides has a distinct (00l) orientation. The target product obtained after doping exhibits superior ferroelectric and piezoelectric properties, see... Figure 8 ,from Figure 8 As can be seen, the ferroelectric remanent polarization intensity reaches 15 μC / cm. 2 The piezoelectric coefficient exceeds 10 pC / N.
[0047] CaBi₂Nb doped with V (vanadium) ions and Ta (tantalum) ions was prepared in Example 1. 2-x V x Ta x Compared with pure CaBi2Nb2O9, the texture and performance of O9 (x value is greater than 0 and less than or equal to 1) are significantly improved after doping.
[0048] Example 2: A method for preparing high-performance self-textured high-temperature piezoelectric ceramics, the specific steps of which are as follows: Step 1: Weigh calcium carbonate, bismuth trioxide, niobium pentoxide, and copper oxide according to a molar ratio of calcium, bismuth, niobium, and copper of 1:2:2-x:x. Then, sequentially add the calcium carbonate, bismuth trioxide, niobium pentoxide, and copper oxide to a mortar and grind them in a dry environment for 2 hours. Place the ground powder into an alumina crucible and heat it to 800 °C in a high-temperature furnace at a heating rate of 3 °C / min, hold it at that temperature for 2 hours, and then allow it to cool in the furnace. Step 2: First, put the pre-calcined powder into a mortar and grind it for 2 hours. Then, put the ground powder into a 15 mm tableting mold and press it into tablets on a tablet press with a pressure of 20 tons. Then, heat it to 900℃ in a high-temperature furnace at a heating rate of 3℃ / min and hold it for 2 hours before furnace cooling and sintering the resulting sheet sample. Step 3: The sintered sheet sample from Step 2 is ground again in a mortar for 2 hours. The ground powder is then placed into a 15 mm tableting mold and pressed into tablets using a tablet press at a pressure of 8 tons. The temperature is then increased to 1050 °C in a high-temperature furnace at a rate of 3 °C / min, held for 4 hours, and then cooled in the furnace to obtain a high-performance self-textured high-temperature piezoelectric ceramic with the structural formula CaBi₂Nb. 2- x Cu x O9 (x takes values greater than 0 and less than or equal to 1).
[0049] Finally, the target product was characterized using scanning electron microscopy and X-ray diffraction, as shown in the figures below. Figure 4 , Figure 5 and Figure 6 As shown. By Figure 4 As can be seen, the XRD spectrum shows that the relative peak intensity of the target product in the (00l) direction is significantly enhanced, indicating that the target product has a strong (00l) texture parallel to the pressing direction. Figure 5 The texture of the target product is shown to be over 90% for doped calcium bismuth niobate ceramics. Figure 6 The results of scanning electron microscopy (SEM) characterization of the target product show that it consists of densely packed particles. Furthermore, samples with high doping concentrations exhibit distinct grain orientation. Figure 5 and Figure 6 It can be seen that the target product obtained by adding oxides has a distinct (00l) orientation. The target product obtained after doping has better ferroelectric and piezoelectric properties.
[0050] Example 2: Copper-doped CaBi₂Nb 2-x Cu x Compared with pure CaBi2Nb2O9, the texture and performance of O9 (x value is greater than 0 and less than or equal to 1) are significantly improved after doping.
[0051] Comparative Example 1 The method of Comparative Example 1 is the same as that of Example 1, except that it is not doped with V (vanadium) ions.
[0052] The prepared CBNO had no texture and its performance was not improved.
[0053] Comparative Example 2 The method of Comparative Example 2 is the same as that of Example 1, except that it is not doped with Ta (tantalum) ions.
[0054] The prepared CBNO had no texture and its performance was not improved.
[0055] By comparing Example 1, Comparative Example 1, and Comparative Example 2, it can be seen that in the method of the present invention, the two conditions of doping with V (vanadium) ions and doping with Ta (tantalum) ions have a synergistic effect, which can synergistically improve the quality of the prepared CaBi2Nb. 2- x V x Ta x The O9 (x value is greater than 0 and less than or equal to 1) exhibits improved texture, ferroelectric properties, and piezoelectric properties. Specifically, in the method of this invention, the doping molar ratio of V (vanadium) ions to Ta (tantalum) ions at 1:1 has a significant synergistic effect, which can significantly improve the prepared CaBi₂Nb. 2-x V x Ta x Texture, ferroelectric properties, and piezoelectric properties of O9 (x values are greater than 0 and less than or equal to 1).
[0056] Comparison with existing technologies: Compared with other texturing techniques that require electric fields, magnetic fields, and stress, the present invention has significant advantages, as shown below: Table 1. Comparison of texture and piezoelectric properties of CBNO piezoelectric ceramics prepared by the present invention and other existing technologies.
[0057] As can be seen from Table 1: 1. This invention can obtain an ultra-high texture degree (Lotgering factor) of over 90% (texture degree is obtained from XRD results, which is a well-known method in the art; the specific formula is: texture degree = (P-P0) / (1-P0), where P = (00l) / (hkl), P0= (00l) / (hkl), where I0 and I are the diffraction peak intensities of the textured sample and the randomly oriented ceramic, respectively, and hkl is the crystal plane index. This is significantly superior to existing techniques (such as the oxide sintering aid method (CN114560698A), whose texture degree is at most about 70%, see... Figure 7 This significantly enhances the preferred orientation of the grains, thus increasing the piezoelectric constant d. 33 Ferroelectric properties and high-temperature stability are synergistically improved, with the ferroelectric remanent polarization reaching 15 μC / cm. 2 The piezoelectric coefficient exceeds 10 pC / N (see Figure 8 ).
[0058] 2. This invention achieves high texture while maintaining a high Curie temperature (≥900℃) (see...). Figure 9 This method simultaneously enhances piezoelectric activity, solving the problem of performance trade-offs in traditional methods. It is particularly suitable for sensor and transducer applications in harsh environments such as high temperatures.
[0059] Although embodiments of the invention have been disclosed for illustrative purposes, those skilled in the art will understand that various substitutions, variations, and modifications are possible without departing from the spirit and scope of the invention and the appended claims. Therefore, the scope of the invention is not limited to the contents disclosed in the embodiments.
Claims
1. A high-performance self-textured high-temperature piezoelectric ceramic, characterized in that: The chemical formula of the piezoelectric ceramic is: Ca 1- x A x Bi 2-y B y Nb 2-z C z O9; where x, y, and z all take values greater than or equal to 0 and less than or equal to 1, and x, y, and z cannot all take the value 0 at the same time; A represents one or more metal ions that substitute for the Ca site; B represents one or more metal ions that substitute for the Bi site; C represents one or more metal ions that substitute for the Nb site; Furthermore, the piezoelectric ceramic is sintered using a conventional solid-state reaction method without adding any oxide sintering aids or applying an electric field, magnetic field, or mechanical stress, and its texture degree is ≥90%.
2. The self-textured high-temperature piezoelectric ceramic according to claim 1, characterized in that: The A is selected from: Li + Na + 、Sr 2+ Ba 2+ Mg 2+ La 3+ 、Nd 3+ 、Sm 3+ One or more of the following; The B is selected from: La 3+ 、Nd 3+ 、Sm 3+ Gd 3+ Y 3+ Ce 3+ Cu 2+ One or more of the following; The C is selected from: Ta 5+ W 6+ V 5+ Ti 4+ Co 6+ Mn 4+ Cu 2+ One or more of them.
3. The self-textured high-temperature piezoelectric ceramic according to claim 1 or 2, characterized in that: The residual polarization of the piezoelectric ceramic reaches 15 μC / cm. 2 The above represents the remanent magnetization of the high-temperature piezoelectric ceramic CaBi₂Nb₂O₉, which is 4.7 μC / cm. 2 More than 3 times that of the CaBi2Nb2O9 high-temperature piezoelectric ceramic; the piezoelectric coefficient reaches 10 pC / N, which is more than 2 times the piezoelectric coefficient of 5 pC / N of the CaBi2Nb2O9 high-temperature piezoelectric ceramic.
4. The application of the piezoelectric ceramic as described in any one of claims 1 to 3 as a piezoelectric device.
5. A method for preparing a piezoelectric ceramic as described in any one of claims 1 to 3, characterized in that: Includes the following steps: Step 1: Weigh calcium carbonate, bismuth trioxide, niobium pentoxide and dopant, and add them to a mortar or ball mill in sequence, and grind for 1-2 hours. Step 2: The ground powder is loaded into an 8-30 mm tableting mold and pressed into tablets on a tableting machine at a pressure of 8-25 tons. Then, it is pre-sintered in a high-temperature furnace and cooled with the furnace after sintering to obtain a sheet sample. Step 3: Grind the sintered sheet sample from Step 2 again in a mortar or ball mill for 1-2 hours. Then, put the ground powder into an 8-30 mm tableting mold and press it into a tableting machine at a pressure of 8-25 tons. Then, heat it to 950-1200 ℃ in a high-temperature furnace at a heating rate of 3 ℃ / min, hold it at that temperature for 3-5 hours, and then cool it in the furnace to obtain the sheet sample, which is the piezoelectric ceramic.
6. The preparation method according to claim 5, characterized in that: In step 1, the molar ratio of calcium, bismuth, niobium, and dopant elements is determined based on the doping location and the type of dopant element.
7. The preparation method according to claim 5, characterized in that: In step 2, the pre-sintering is a one-step sintering, a two-step sintering, or a three-step sintering, with a sintering temperature of 800-1200 ℃, a sintering time of 2-5 h, and a heating rate controlled at 3-5 ℃ / min.
8. The preparation method according to any one of claims 5 to 7, characterized in that: The method further includes step 4: depending on the requirements, the sheet sample sintered in step 3 is ground again in a mortar or ball mill for 1-2 hours, and then the ground powder is loaded into an 8-30 mm tableting mold and pressed into tablets on a tableting machine at a pressure of 8-25 tons; then the temperature is raised to 1000-1200 ℃ in a high-temperature furnace at a heating rate of 3 ℃ / min, held for 3-5 hours, and then cooled in the furnace to obtain piezoelectric ceramics.
Citation Information
Patent Citations
Method for enhancing performance of calcium bismuth niobate high-temperature piezoelectric ceramic through oxide sintering aid induced texture
CN114560698A